Investigations on postnatal development of the foliate papillae of the tongue by the light and scanning electron microscopy in the white laboratory mice - Toprak, B.; Yilmaz (Ecole Nationale Veterinaire Toulouse, 2007)
The postnatal development and structure of foliate papillae of the tongue were examined by the light and scanning electron microscope in the mice. In that aim, the animals were divided into eight groups according to their age (0, 15, 30, 60, 90, 120, 150 and 180 days, n=8 per group). Foliate papillae were located between the body and the radix of the tongue at the caudo-lateral sides of it. Foliate papillae grooves started to open at day 3 and were completely opened at postnatal day 8. Taste buds with developed pores were seen at this stage. Two different, light and dark cells of taste buds were distinguished in taste buds. The foliate papillae developed more rapidly during the first 30 days than between day 30 and day 90 and completed their development at day 90. Foliate papillae were shown to exhibit mucosal crypts rather than laminas by scanning electron microscope. The thickness of epithelial border cells was apparent with high magnification. There were lots of micro-ridges on the surface of these cells. In conclusion, it was shown that foliate papillae of the tongue achieved their development at day 90 and that taste buds became functional at day 8 day. No differences were evidenced on the surface structure of the papillae from the birth to the adulthood period in mice.
Keywords: development; foliate papillae; mice; scanning electron microscope